Forty years of debris-flow monitoring at Kamikamihorizawa Creek, Mount Yakedake, Japan - Suwa, Hiroshi; Okano, Kazuyuki; Kanno, Tadahiro (Italian journal of engineering geology and environment, 2011)
<span data-sheets-value="{"1":2,"2":"Kamikamihorizawa Creek on the slopes of Mount Yakedake, Nagano Prefecture, was selected as a monitoring site for debris flows considering a high frequency of debris flow and instrumented with monitoring equipments in 1970: eight years after the last phreatic explosion of this volcano. The monitoring system was improved by adding speedometers, stage meters, seismometers and so on, in addition to the off-line monitoring surveys on the interaction between debris flows, hillslope hydrology and slope morphology. During the last 40 years, data were obtained from 91 debris- flow events that contained more than 200 episodes of debris- flow surges. Studies from the data supplied a general concept of the debris-flows and their geomorphic effects at volcanic slopes as follows. Debris flows are triggered by a large intensity of rainfall in a short duration as much as 10 minute. Threshold of rainfall intensity for debris flows increases with time after the end of volcanic eruption, while it drastically decreases with the eruption. Three types of debris ows were found: Large ows with boulder dam without open- work structure (Type I), small ows with boulder dam with openwork structure (Type II), and small ows with boulder dam without openwork structure (Type III). Rainfall conditions were found to have controlled the difference between these types through water availability to debris flows at the source and growth reaches of debris flows. Mass and boulder focusing to the flow front are marked, and due to this focusing\rthe flow radiates elastic waves whose energy is from the potential energy of the flow. The energy conversion efficiency from the potential energy to elastic wave energy is a magnitude of 10-3 much smaller than the efficiency for earthquake at 10-1 from the strain energy to the elastic-wave energy. Debris flows terminate in the fan leaving two types of debris- flow lobes: swollen lobes and flat lobes. Main source of the flat lobes is attributed to the Types I and III, while the swollen lobe to the Type II. It would be important to understand this concept for volcanic debris flows from its initiation to termination for the mitigation of debris-flow hazards."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">Kamikamihorizawa Creek on the slopes of Mount Yakedake, Nagano Prefecture, was selected as a monitoring site for debris flows considering a high frequency of debris flow and instrumented with monitoring equipments in 1970: eight years after the last phreatic explosion of this volcano. The monitoring system was improved by adding speedometers, stage meters, seismometers and so on, in addition to the off-line monitoring surveys on the interaction between debris flows, hillslope hydrology and slope morphology. During the last 40 years, data were obtained from 91 debris- flow events that contained more than 200 episodes of debris- flow surges. Studies from the data supplied a general concept of the debris-flows and their geomorphic effects at volcanic slopes as follows. Debris flows are triggered by a large intensity of rainfall in a short duration as much as 10 minute. Threshold of rainfall intensity for debris flows increases with time after the end of volcanic eruption, while it drastically decreases with the eruption. Three types of debris ows were found: Large ows with boulder dam without open- work structure (Type I), small ows with boulder dam with openwork structure (Type II), and small ows with boulder dam without openwork structure (Type III). Rainfall conditions were found to have controlled the difference between these types through water availability to debris flows at the source and growth reaches of debris flows. Mass and boulder focusing to the flow front are marked, and due to this focusing the flow radiates elastic waves whose energy is from the potential energy of the flow. The energy conversion efficiency from the potential energy to elastic wave energy is a magnitude of 10-3 much smaller than the efficiency for earthquake at 10-1 from the strain energy to the elastic-wave energy. Debris flows terminate in the fan leaving two types of debris- flow lobes: swollen lobes and flat lobes. Main source of the flat lobes is attributed to the Types I and III, while the swollen lobe to the Type II. It would be important to understand this concept for volcanic debris flows from its initiation to termination for the mitigation of debris-flow hazards.